2012
DOI: 10.1016/j.jtcvs.2011.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Failure of remote ischemic preconditioning to reduce the risk of postoperative acute kidney injury in children undergoing operation for complex congenital heart disease: A randomized single-center study

Abstract: We found no evidence that remote ischemic preconditioning provided protection of kidney function in children undergoing operation for complex congenital heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 24 publications
2
52
0
3
Order By: Relevance
“…Thus, the trial of leg preconditioning in children undergoing surgery for complex congenital cardiac disease found no evidence that rIPC protected renal function. 73 End points were AKI development, initiation of dialysis, plasma creatinine, eGFR, plasma cystatin C, plasma and urinary neutrophil gelatinase-associated lipocalin, and urinary output. Similar results were reported by another study on 76 patients undergoing complex valvular heart surgery.…”
mentioning
confidence: 99%
“…Thus, the trial of leg preconditioning in children undergoing surgery for complex congenital cardiac disease found no evidence that rIPC protected renal function. 73 End points were AKI development, initiation of dialysis, plasma creatinine, eGFR, plasma cystatin C, plasma and urinary neutrophil gelatinase-associated lipocalin, and urinary output. Similar results were reported by another study on 76 patients undergoing complex valvular heart surgery.…”
mentioning
confidence: 99%
“…Cystatin C and NGAL as novel biomarkers have not been used and validated in animal studies. Nevertheless, they have recently been reported as early detectors of renal failure in clinical setups of RIPC [23,24,26,38,39,40]. In all these clinical studies, no benefit of RIPC has been found.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 13 clinical trials including patients who underwent cardiac and vascular interventions, RIPC was considered as potentially beneficial for the prevention of acute kidney injury, but the currently available information is not robust enough to make a recommendation [22]. However, other studies have not demonstrated a protective effect of RIPC against renal impairment after various procedures, such as infrarenal AAA repair [23] and heart surgery in adults [24], children [25] or neonates [26]. …”
Section: Introductionmentioning
confidence: 99%
“…В 2012 г. опубликованы результаты клинических наблюде-ний 113 детей (возраст от 0 до 15 лет), которым выполнялась хи-рургическая коррекция пороков сердца [54]. Поражение почек оценивали по нескольким показателям: СКФ, содержание в плазме крови креатинина, NGAL и цистатина-С, концентрация в моче NGAL.…”
Section: терапевтический архив 8 2016unclassified
“…Поражение почек оценивали по нескольким показателям: СКФ, содержание в плазме крови креатинина, NGAL и цистатина-С, концентрация в моче NGAL. Установлено, что ДИП не влияет ни на один из ука-занных показателей [54]. Год спустя B. Jones и соавт.…”
Section: терапевтический архив 8 2016unclassified